Detection of teeth surface defects using fiber optic displacement sensor / Adi Izhar Che Ani - Adi Izhar, Che Ani (2012)
Fiber optic displacement sensor has been used recently for general medical diagnostics and in industry for the characterization and detection of defects in engineering components. However the lack of understanding of parameter performance of such a sensor in teeth has largely precluded its application to dentistry. This research describes sensor system adopting an intensity modulation technique that used a concentric type bundled optical fiber as a probe in conjunction with the real teeth, artificial teeth, hybrid composite resin teeth and mirror as the reflecting targets. The performance of the sensor is investigated on the linear range, sensitivity and the peak position. In this experiment, the sensor system is used for detecting defect on real teeth. A 2 mm hole is drilled to create defect on the teeth surface to stimulate dental cavity. The sensor probe is consequently fixed within the linear range of the displacement and the intensity of the collected light as a function of lateral movement (x and y axis) of the teeth surface is recorded while being maintained in perpendicular and constant in axial position (z axis). The image surface of the defect teeth is reconstructed from the recorded output voltage using the MATLAB software. This method is practically suitable when used in conjunction with a micro-computed tomography system in determining the defect of surface profile of a 3D tomography object being inspected prior to the image reconstruction.